2021
DOI: 10.1111/1365-2664.14067
|View full text |Cite
|
Sign up to set email alerts
|

Populations restored using regional seed are genetically diverse and similar to natural populations in the region

Abstract: Ecological restoration and plant re‐introductions aim to create plant populations that are genetically similar to natural populations to preserve the regional gene pool, yet genetically diverse to allow adaptation to a changing environment. For this purpose, seeds for restoration are increasingly sourced from multiple populations in the target region. However, it has only rarely been tested whether using regional seed indeed leads to genetically diverse restored populations which are genetically similar to nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 81 publications
0
25
0
Order By: Relevance
“…The species flowers only after the restored meadows are mown, and there is thus no opportunity for selection. It also grows in a wide range of conditions (Leuschner & Ellenberg, 2018), and is one of the few species that can thrive in grassland restorations in unfavorable postarable soils (Klein-Raufhake et al, 2022.). Thus, it is possible that Centaurea has such a wide ecological niche that the environment at restored meadows is not challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species flowers only after the restored meadows are mown, and there is thus no opportunity for selection. It also grows in a wide range of conditions (Leuschner & Ellenberg, 2018), and is one of the few species that can thrive in grassland restorations in unfavorable postarable soils (Klein-Raufhake et al, 2022.). Thus, it is possible that Centaurea has such a wide ecological niche that the environment at restored meadows is not challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental differences between natural and restored sites might be mirrored by intraspecific differences in plant phenotypes. For example, Klein-Raufhake et al (2022) have shown that plants from grasslands restored 20 years ago are smaller and have different leaf chemical composition in comparison to the same species growing in natural populations, which correlates with the differences in soil chemistry due to post-agricultural legacy in restored sites. This pattern may be a simple plastic reaction to environmental conditions (Villellas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The top 40 cm of phosphate‐enriched soil on a total of 250 ha was excavated. The development of the target vegetation was facilitated by liming (1000 kg/ha) and transfer of freshly cut clippings on the excavated areas from the nearby nature reserve (Donath et al, 2007 ; Höfner et al, 2021 ; Hölzel & Otte, 2003 ; Matus et al, 2003 ; Török et al, 2011 ). Starting 1 year later, all restored meadows were mown yearly in summer.…”
Section: Methodsmentioning
confidence: 99%
“…For certain groups of organisms, translocation offers a possibility for successful colonization into the restored new habitats. For example, plant species have been moved to newly established patches of habitat by transportation of seeds or young plants (Donath et al, 2007 ; Goreth et al, 2021 ; Török et al, 2021 ; Vitt et al, 2016 ; Wagner et al, 2021 ), preferably from sites with a common genetic background (Höfner et al, 2021 ). Moreover, birds, mammals, amphibians, and some butterflies are also translocated as soon as the new patches have developed into suitable habitats (Ferrer et al, 2017 ; Germano & Bishop, 2009 ; Wynhoff, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of their high natural value, grasslands have been plowed and converted to cropland on a large scale in the past. The demand for arable land has recently decreased, but the restoration of species‐rich grassland communities on former arable land is problematic worldwide because it does not reach the state of the reference ecosystems (Kiehl et al, 2010; Brudvig, 2011; Török et al, 2011; Höfner et al, 2022).…”
Section: Introductionmentioning
confidence: 99%